On the genetic classification and tectonic implications of the Early Yanshanian granitoids in the Nanling Range, South China - Li, X.; Li, W.; Li, Zheng-Xiang (Science in China Press/Zhongguo Kexue Zazhishe, 2007)
Early Yanshanian (Jurassic) granitoids are widespread in the Nanling Range of South China, and are associated with numerous non-ferrous and rare metal mineral deposits. These granitoids consist mainly of slightly peraluminous biotite monzogranites and K-feldspar granites that are closely associated in time and space with subordinate amphibole-bearing granites and muscovite- and garnet-bearing granites. In most previous studies, the biotite-bearing granites were classified as crustal transformation-type (corresponding to the S-type) granites which were interpreted to be derived from the regional Paleoproterozoic meta-sedimentary rocks. In this paper, we re-analyze the geochemical characteristics of a number of representative Early Yanshanian Nanling granitoids. There exists a clear negative correlation between SiO2 and P2O5 for the studied granitoids. The Early Yanshanian Nanling granitoid suites (including amphibole-bearing granodiorites->biotite monzogranites->K-feldspar granites->two-mica (muscovite) granites) are metaluminous to slightly peraluminous I-type or fractionated I-type granites. They were derived predominantly from Proterozoic igneous protoliths. The juvenile crust and/or newly mantle-derived materials might also have been involved in some of these granites. In addition, the I- and fractionated I-type granites are closely associated in time and space with minor amount of A-type felsic and mafic volcanic and intrusive rocks as well as alkaline rocks. All these rocks constitute a typical assemblage of anorogenic, intraplate magmatism, suggesting a dominant lithospheric extensional regime for the Nanling Range and neighboring region during the Early Yansanian period.